667 Effect of short-term exposure of asbestos on human t cell line mt-2. (24th April 2018) - Matsuzaki, H; Lee, S; Maeda, M; Kumagai-takei, N; Yoshitome, K; Nishimura, Y; Otsuki, T
Abstract : Introduction: Asbestos fibres cause mesothelioma and lung cancer. We propose that asbestos suppress anti-tumour immune system in addition to transformation of mesothelial and lung epithelial cells. It is reported that asbestos induces apoptosis of epitherial cells through various processes such as, mitochondrial dysfunction, DNA damage, ER stress. On the other hand, we proposed that asbestos fibres affects on immune cells to attenuate immune response to tumour cells. We employed MT-2 cells as a model of Treg and maintained them with low concentration of asbestos for longer than 8 months. MT-2 cells exposed with low-concentration asbestos for long term showed higher viability after treatment with high concentration of asbestos than original MT-2 cells, and they were designated as MT-2Rst. However, it is still unclear how asbestos induces apoptosis of MT-2 cells and molecular basis of resistance of MT-2Rst cells to high concentration of asbestos. Methods: We analysed acute effect of asbestos on mitochondria using mitochondrial membrane potential indicator JC-1 dye and immunoblot analysis using antibodies recognising DNA damage markers. Result: It was found that asbestos fibres induced loss of mitochondrial membrane potential and phosphorylation of Histone H2AX, a marker protein of DNA damage. Discussion: These data suggest that asbestos fibres induces apoptosis of MT-2 cells through the mitochondrial dysfunction and DNA damage, and these apoptotic pathways are modified in MT-2Rst cells.